PENDAMPINGAN PENGELOLAAN GULA AREN DI DESA BONTO: Assistance in Palm Sugar Management in Bonto Village - Fajri, Fajri; Qadrianti, Laeli (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2024)
Abstract: Palm sugar production is one of the livelihoods of the people in Bonto village which still really needs guidance in its management. The low selling value and lack of creativity in the products of palm sugar farmers who only focus on solid palm sugar make it difficult for them to market their products to the outside community. Seeing the problems of palm sugar farmers and the large number of palm trees that must be managed makes the author interested in carrying out community service, namely managing palm sugar which aims to provide solutions that can improve the economy of palm sugar farmers in Bonto village. The method for implementing this activity is providing assistance for innovation in making palm sugar. In carrying out activities, survey and mentoring methods are used which emphasize the involvement of palm sugar farmers (partners) in all activities including planning, implementation and evaluation of activity programs. The result of this activity is that partners are able to make and improve the quality of Semut Sugar (palm sugar) products so that they can show new variations in palm sugar products and carry out wider sales. In this way, product development assistance is also expected to continue to help the community's economy as well as the government of Bonto Village, Central Sinjai District and the Regional Government of Sinjai Regency to produce superior village products.  Keywords: Management; Palm Sugar; Bonto Village   Abstrak: Produksi gula aren sebagai salah satu mata pencaharian masyarakat di desa Bonto yang masih sangat membutuhkan pembinaan dalam pengelolaannya. Rendahnya nilai jual dan kurangnya kreatifitas produk petani gula aren yang hanya terfokus pada gula aren padat menyebabkan mereka sulit untuk memasarkan hasil produk kepada masyarakat luar. Melihat dari permasalahan petani gula aren serta banyaknya pohon aren yang harus dikelola membuat penulis tertarik untuk melakukan pengabdian masyarakat yaitu pengelolaan gula aren yang bertujuan untuk memberikan solusi yang dapat meningkatkan perekonomian para petani gula aren di desa Bonto. Metode pelaksanaan kegiatan ini adalah pemberian Pendampingan Inovasi Pembuatan Gula Semut (Palm sugar). Dalam pelaksanaan kegiatan menggunakan metode survei dan pendampingan yang menekankan keterlibatan petani gula aren (mitra) dalam keseluruhan kegiatan meliputi perencanaan, pelaksanaan dan evaluasi program kegiatan. Hasil dari kegiatan ini adalah mitra mampu membuat dan meningkatkan kualitas produk Gula Semut (palm sugar) sehingga dapat menunjukkan fariasi baru dalam produk gula aren serta melakukan penjualan yang lebih luas. Dengan demikian pendampingan pengembangan produk juga diharapkan tetap berjalan agar membantu perekonomian Masyarakat serta pemerintah Desa Bonto Kecamatan Sinjai Tengah dan Pemerintah Daerah Kabupaten Sinjai untuk menghasilkan produk unggulan Desa. Kata kunci: Pengelolaan; Gula Aren; Desa Bonto